2022
DOI: 10.3389/fmolb.2022.1001508
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of the antimicrobial peptide LyeTx I-b maintains structure-related biological properties and improves selectivity

Abstract: The biological activity of antimicrobial peptides and proteins is closely related to their structural aspects and is sensitive to certain post-translational modifications such as glycosylation, lipidation and PEGylation. However, PEGylation of protein and peptide drugs has expanded in recent years due to the reduction of their toxicity. Due to their size, the PEGylation process can either preserve or compromise the overall structure of these biopolymers and their biological properties. The antimicrobial peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Compared to the parent IDR1018 peptide, which appeared to be hemolytic against RBCs as well as toxic to PBMCs at high doses (up to 20% at 128 µg mL −1 ), neither of the conjugated derivatives exhibited any hemolysis or cytotoxicity at the highest concentration tested (Figure 2a,b). Consistent with other previous studies for other peptides [30,31,42,43], pegylation and glycosylation worked well in reducing HDP toxicity. The capacity of conjugated peptide derivatives to modulate the innate immune system was tested by assessing the induction and suppression of chemokines and cytokines from human PBMCs.…”
Section: Hemolysis Cytotoxicity and Immunomodulatory Activitysupporting
confidence: 91%
“…Compared to the parent IDR1018 peptide, which appeared to be hemolytic against RBCs as well as toxic to PBMCs at high doses (up to 20% at 128 µg mL −1 ), neither of the conjugated derivatives exhibited any hemolysis or cytotoxicity at the highest concentration tested (Figure 2a,b). Consistent with other previous studies for other peptides [30,31,42,43], pegylation and glycosylation worked well in reducing HDP toxicity. The capacity of conjugated peptide derivatives to modulate the innate immune system was tested by assessing the induction and suppression of chemokines and cytokines from human PBMCs.…”
Section: Hemolysis Cytotoxicity and Immunomodulatory Activitysupporting
confidence: 91%
“…conjugation targeted site-specific amino acids, including lysine (Lys), Cys, arginine (Arg), and Tyr, which can increase the molecular size of the peptide. PEGylation has been reported to increase oxytocin stability at high temperatures [ 124 ], extending the biological activities of Human Pancreatic Polypeptide (hPP) [ 151 ] and minimizing side effects of antimicrobial peptides LyeTx I-b [ 152 ]. Although it is rare, it has been found that patients can develop allergic reactions to P.E.G.…”
Section: Strategies To Optimize Peptide Stability In Aqueous Formulat...mentioning
confidence: 99%
“…Other strategies include (i) PEGylation [ 39 , 40 ], which allows for greater solubility and stability in aqueous solutions while reducing renal clearance [ 41 ]; (ii) glycosylation involving carbohydrate conjugation, which broadens peptide diversity by extending their properties and functions [ 42 ]; and (iii) lipidation involving the covalent attachment of fatty acids, which affects peptide activity through several mechanisms [ 43 , 44 ].…”
Section: Structural Modification Of Ampsmentioning
confidence: 99%